Rare cause of severe hematemesis due to IgG4-related gastric ulcer - He, Yu-Qin; Fu, Xin; Chen, Dong-Feng (Turkish Journal of Gastroenterology, 2019)
Cite this article as: He YQ, Fu X, Chen DF. Rare cause of severe hematemesis due to IgG4-related gastric ulcer. Turk J Gastroenterol 2019; 30(10): 925-7.